2014
DOI: 10.12691/ajmsm-2-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and Its Role in the Development of Oxidative Stress and DNA Damage: An Insight

Abstract: Alcohol is detoxified in the liver by the enzymes alcohol dehydrogenase and aldehyde dehydrogenase. The available literature suggests that activity of aldehyde dehydrogenase is less than alcohol dehydrogenase among Asians; hence it leads to accumulation of acetaldehyde during excess intake of alcohol. Accumulated acetaldehyde due to its electrophilic nature forms adducts with proteins and DNA. The acetaldehyde-DNA adduct (N-2-Ethyl deoxyguanosine (NDG)) induces mutations in DNA and leads to DNA damage. Prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Clinically, the induction of sustained or periodic hypoglycemia at levels below 85 mg/dL in humans can occur in settings of liver failure, congestive heart failure, malnutrition and anorexia, cancerassociated cachexia and wasting, lupus, chronic alcoholism, and with certain medications [60][61][62][63][64][65][66][67] . Low glucose is a potent signal to decrease insulin production by β-cells, contributing to the onset of hypoinsulinemic hypoglycemia 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the induction of sustained or periodic hypoglycemia at levels below 85 mg/dL in humans can occur in settings of liver failure, congestive heart failure, malnutrition and anorexia, cancerassociated cachexia and wasting, lupus, chronic alcoholism, and with certain medications [60][61][62][63][64][65][66][67] . Low glucose is a potent signal to decrease insulin production by β-cells, contributing to the onset of hypoinsulinemic hypoglycemia 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all fractions, the highest concentration of polyphenols, flavonoids, and tannins was observed in methanol extracts from skin compared with other extracts from skin, pulp, and seeds, while methanol extracts from skin and pulp exhibited the greatest antioxidant activities. Lymphoma cells were treated with all extracts of Annona fractions at increasing concentrations (0, 10,25,50,75,100,150,200 and 300 µg/mL). The results of this study showed that water and chloroform skin extracts had no significant antiproliferative effect on Ramos-1 lymphoma cells, whereas methanol skin extract had a significant inhibitory effect on cell proliferation, with a dose-dependent effect of up to 75 µg/mL, resulting in the death of 60% of total cells.…”
Section: Lymphoma Diet and Oxidative Stressmentioning
confidence: 99%
“…Nutrition-mediated oxidative stress plays a significant role in the development of cancer. Some dietary components have a relationship with oxidative stress and, as a result, with carcinogenesis; for instance, alcohol causes biological signaling molecules to malfunction by increasing ROS production while decreasing cellular antioxidant levels [ 99 ], also causes acetaldehyde accumulation [ 100 ], and induces mitochondrial dysfunction resulting in cell death [ 101 ]. It has also been seen that a high-carbohydrate meal can result in increased oxidative stress [ 102 ]; in fact, postprandial hyperglycemia results, both in normal subjects and those with diabetes, in an imbalance in the ratio of NADH to NAD and increased non-enzymatic glycation in cells which leads to the formation of free radicals [ 103 , 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considerando isso, os efeitos glicêmicos não são considerados efeitos marcantes proveniente da administração de cetamina. Por outro lado, o processo de biotransformação do etanol envolve sucessivas oxidações dependentes da presença de NAD + resultando em um aumento da razão NAD + /NADH (Rang et al, 2004), sabendo que a via gliconeogênica também ocorre no fígado e é igualmente dependente dos níveis de NAD + disponíveis, portanto, o aumento dessa razão (NAD + /NADH) promovido pelo consumo de etanol, diminui a capacidade de funcionamento desta via resultando em hipoglicemia (HAMMERSTEDT et al, 2011;KANDIet al, 2014a;KANDI et al, 2014b).…”
Section: Estudo Neuroquímico Dos Animais Tratados Por 28 Diasunclassified